Tinjauan Yuridis Aborsi Bagi Korban Pemerkosaan Berdasar Hukum Kesehatan dan Hukum Pidana - Muhammad Arif Nur Syahid (Universitas Palangka Raya, 2024)
This paper examines the legal review of abortion actions for victims of rape based on the Health Law and criminal law in Indonesia. Using a normative juridical method, this study analyzes the paradigm shift in the regulation of abortion, where the Health Law provides a legal basis for legal abortion in cases of rape. The results of the analysis show the potential for a conflict of norms between the Health Law and criminal law, which requires further harmonization. The implementation of legal abortion for victims of rape still faces challenges, including a lack of understanding and social stigma. This research concludes the need for a multidisciplinary approach in handling cases of abortion for victims of rape, and recommends law harmonization, the preparation of detailed implementing regulations, and public education to improve legal protection for victims and health workers.